Critical Assessment of the Important Residues Involved in the Dimerization and Catalysis of MERS Coronavirus Main Protease - Ho, Bo-Lin (PLoS One, 2015)
BACKGROUND: A highly pathogenic human coronavirus (CoV), Middle East respiratory syndrome coronavirus (MERS-CoV), has emerged in Jeddah and other places in Saudi Arabia, and has quickly spread to European and Asian countries since September 2012. Up to the 1(st) October 2015 it has infected at least 1593 people with a global fatality rate of about 35%. Studies to understand the virus are necessary and urgent. In the present study, MERS-CoV main protease (M(pro)) is expressed; the dimerization of the protein and its relationship to catalysis are investigated. METHODS AND RESULTS: The crystal structure of MERS-CoV M(pro) indicates that it shares a similar scaffold to that of other coronaviral M(pro) and consists of chymotrypsin-like domains I and II and a helical domain III of five helices. Analytical ultracentrifugation analysis demonstrated that MERS-CoV M(pro) undergoes a monomer to dimer conversion in the presence of a peptide substrate. Glu169 is a key residue and plays a dual role in both dimerization and catalysis. The mutagenesis of other residues found on the dimerization interface indicate that dimerization of MERS-CoV M(pro) is required for its catalytic activity. One mutation, M298R, resulted in a stable dimer with a higher level of proteolytic activity than the wild-type enzyme. CONCLUSIONS: MERS-CoV M(pro) shows substrate-induced dimerization and potent proteolytic activity. A critical assessment of the residues important to these processes provides insights into the correlation between dimerization and catalysis within the coronaviral M(pro) family.